Perbandingan Hasil Investasi Reksa Dana Saham dengan Metode Lump Sum Dan Dollar Cost Average : Studi Kasus Reksa Dana Panin Dana Maksima - Taofik Hidajat (EBBANK, 2014)
Market conditions change sometimes makes investors wonder about when it is appropriate to buy mutual funds and what strategies can be done to reduce the risk of loss. In addition, there are no established guidelines regarding the proper timing to enter the market through mutual funds so that the investment strategy needs to be done in order to obtain optimal results.Some investment strategies are becoming the object of such research is Dollar Cost Average (DCA), Value Average (VA) and the Lump-Sum (LS). Various studies to examine the investment strategy also has been done.Background of the results of research on investment strategies vary and are still at least some research on the Indonesian Stock Exchange, the questions raised in the study is whether there is a difference between the investment strategy of the Lump Sum (LS) with Dollar Cost Average (DCA).The object of analysis is an equity fund Panin Dana Maksima began in January 2011 to August 2013. To test the difference between the LS with DCA, performed statistical analysis, namely the Wilcoxon Signed Rank Test.The results of this study by using the mutual fund Panin Dana Maksima indicate that LS strategy gives results that are generally better than the DCA. Nevertheless, the results of statistical analysis showed that there is no difference between LS investment results with DCA.